Projection of Effectiveness, Efficiency, and Regional Independence of Gorontalo Province - Rasid, Ayub Usman; Masia, Israwanto; Hasyim, Hasyim (Universitas Gorontalo, 2025)
This article examines the projection of Gorontalo Province's financial performance in the context of the decentralization of the Indonesian government that has been going on since 1999. Although decentralization provides greater autonomy in the management of resources and public services, Gorontalo Province still faces significant challenges in optimizing Regional Original Revenue (PAD) and a high dependence on fund transfers from the central government. Using a quantitative approach and descriptive methods, this study analyzes secondary data from the Gorontalo Governor's Accountability Report (LKPJ) for the 2019-2023 period. The analysis was carried out using three financial ratios – effectiveness, efficiency, and regional independence – which were then projected for the 2024-2033 period using linear trend analysis. The projection results show interesting dynamics: a decrease in the effectiveness ratio from 99.50% to 39.71%, an increase in efficiency from the status of